2023
DOI: 10.1021/acs.inorgchem.2c03432
|View full text |Cite
|
Sign up to set email alerts
|

(C5N2H14)GeBr4: A 2D Organic Germanium Bromide Perovskite with Strong Orange Photoluminescence Properties

Abstract: Hybrid organic−inorganic metal halide (OIMH) perovskites are regarded as potential photoluminescent (PL) materials and have attracted intensive attention. Here, we select 1-methylpiperazine as an organic component and successfully obtain a two-dimensional (2D) Ge-based OIMH perovskite, (1-mpz)GeBr 4 . It features a 2D layered structure composed of distorted [GeBr 6 ] 4− octahedra with organic (C 5 H 14 N 2 ) 2+ located between the layers. (1-mpz)GeBr 4 exhibits strong orange color under ultraviolet (UV) light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…As illustrated in Fig. 3a, the title compound single crystals are transparent with a prism shape, whereas they exhibit two PL emissions under 290 nm UV irradiation: high energy narrow emission (360 nm) corresponding to the UV-vis absorption edge (350 nm) is due to the synergic emissions of free exciton (FE) states, which is highly similar to those of reported low-dimensional organic-in-organic hybrids, such as (N-AD)PbCl 4 (N-AD: N-acetylethylenediamine, C 4 H 10 N 2 O), 41 (1-mpz)GeBr 4 (1-mpz = (C 5 N 2 H 14 ) 2+ ), 42 (homopiperazine)PbBr 4 , 43 (2,6dimethylpiperazine) 3 Pb 2 Br 10 , 43 and (benzimidazole) 2 PbCl 4 . 44 Another low-energy broadband emission has been detected at 640 nm.…”
Section: Photoluminescencesupporting
confidence: 82%
“…As illustrated in Fig. 3a, the title compound single crystals are transparent with a prism shape, whereas they exhibit two PL emissions under 290 nm UV irradiation: high energy narrow emission (360 nm) corresponding to the UV-vis absorption edge (350 nm) is due to the synergic emissions of free exciton (FE) states, which is highly similar to those of reported low-dimensional organic-in-organic hybrids, such as (N-AD)PbCl 4 (N-AD: N-acetylethylenediamine, C 4 H 10 N 2 O), 41 (1-mpz)GeBr 4 (1-mpz = (C 5 N 2 H 14 ) 2+ ), 42 (homopiperazine)PbBr 4 , 43 (2,6dimethylpiperazine) 3 Pb 2 Br 10 , 43 and (benzimidazole) 2 PbCl 4 . 44 Another low-energy broadband emission has been detected at 640 nm.…”
Section: Photoluminescencesupporting
confidence: 82%
“…According to previous literature reports, when perovskite materials are irradiated with UV light, the generated excitons can interact with the crystal lattice, causing lattice distortion and electron–phonon coupling . These excitons tend to be trapped in the lattice potential well, leading to the emission of self-trapped excitons (STEs), which is characterized by a large Stokes shift and a broad emission spectrum. , On the basis of the observed luminescence characteristics, we attribute the LE emission peak at 550 nm of PCl to the emission of STEs ,, and the HE band at 430 nm to the emission of the free excitons (FEs) of the organic cations . The greenish-yellow broad emission of PBr is believed to arise from the STEs of the perovskites …”
Section: Resultsmentioning
confidence: 97%
“…In addition, the infrared spectra of PCl and PBr show that N−H bond stretching vibration signals are observed at 3400, 3049, 3014, and 2933 cm −1 and that N− H bending vibration signals appear at 1610, 1528, 1457, and 1375 cm −1 (Figure S4). 25 It is worth noting that environmental stability, including resistance to moisture, light, and temperature, is crucial for the application of OIHPs. To assess the ambient stability of our OIHP materials, the freshly synthesized PCl and PBr microcrystals were exposed to air for two months before being subjected to PXRD analysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated that rare earth ions form a number of hybrid double perovskite materials, and when appropriate symmetry conditions are met, these materials exhibit useful physical and chemical properties. ,,, Several studies have focused on harnessing the unique optical and magnetic properties of the rare earth ions into hybrid double perovskites. , When the characteristic centrosymmetry of these materials was broken in subsequent experiments, typically by inclusion of asymmetric cations at the A-site, multiferroic properties manifest in addition to the useful properties imparted to the structure by the presence of rare earths. ,, …”
Section: Introductionmentioning
confidence: 99%